2019
DOI: 10.1186/s13075-019-1999-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of rheumatoid arthritis patients reveals an association between innate and adaptive cell populations and response to anti-tumor necrosis factor

Abstract: BackgroundThe goal of this study is to use comprehensive molecular profiling to characterize clinical response to anti-TNF therapy in a real-world setting and identify reproducible markers differentiating good responders and non-responders in rheumatoid arthritis (RA).MethodsWhole-blood mRNA, plasma proteins, and glycopeptides were measured in two cohorts of biologic-naïve RA patients (n = 40 and n = 36) from the Corrona CERTAIN (Comparative Effectiveness Registry to study Therapies for Arthritis and Inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
5
16
1
Order By: Relevance
“…This nding corroborates a recent study which showed that patients treated with anti-TNF in combination with methotrexate decreased the blood neutrophil counts regardless of their clinical response to therapy [48,49]. Additionally, our results also corroborate with earlier studies showing an induction of B cells and NK cells in whole blood following anti-TNF treatment [50]. Along with these changes we also see an upregulation of the proportion of activated NK cells (NKp44+) in responders that express the inhibitory protein NKG2A.…”
Section: Discussionsupporting
confidence: 93%
“…This nding corroborates a recent study which showed that patients treated with anti-TNF in combination with methotrexate decreased the blood neutrophil counts regardless of their clinical response to therapy [48,49]. Additionally, our results also corroborate with earlier studies showing an induction of B cells and NK cells in whole blood following anti-TNF treatment [50]. Along with these changes we also see an upregulation of the proportion of activated NK cells (NKp44+) in responders that express the inhibitory protein NKG2A.…”
Section: Discussionsupporting
confidence: 93%
“…Patients who do not respond to conventional DMARDs usually initiate therapy with TNF inhibitors. However, approximately 30-40% of RA patients fail to respond to anti-TNF therapy and are usually obliged to go several rounds of drug combinations (Farutin et al, 2019). Due to the complex nature of the disease, systems biology and integrative approaches are needed in order to gain insight into the disease pathogenesis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who do not respond to conventional DMARDs usually initiate therapy with TNF inhibitors. However, approximately 30–40% of RA patients fail to respond to antiTNF therapy and are usually obliged to undergo several rounds of drug combinations [9].…”
Section: Introductionmentioning
confidence: 99%
“…The most represented assay is RNA-Seq (n=457, 65%) for the identification of biomarkers in blood or synovial tissue, for example, to distinguish active versus inactive/low disease activity states, 27 to examine response to anti-TNF therapy in RA, 34 to identify gene expression signatures correlating with disease phenotype, 35 for longitudinal analysis of peripheral blood TCR diversity in patients with SLE, 36 as well as for subgrouping patients with SLE with common clinical characteristics, 28 characterisation of circulating memory stem T cells in RA, 37 as well as to examine the BCR repertoire in patients with RA to identify B cell clones associated with autoreactivity. 38 In addition to messenger RNA, a wide range of RNA types can be measured, such as microRNAs (miRNAs) in RA, 39 JIA, 40 SLE and Sjögren’s syndrome, 41 long non coding RNA (lncRNA) in SLE 42 as well as myositis, 43 and finally circular RNA as biomarker in SLE 44 .…”
Section: Resultsmentioning
confidence: 99%